Uma história dos compêndios didáticos Tesouro de Meninos e Tesouro de Meninas no Brasil. - Lima., Jocilene Pereira (2013)
This dissertation had as study corpus the didactic compendia Tesouro de Meninos and Tesouro de Meninas aiming at investigating specifically the circulation of French compendia in Brazilian territory from traces of instituted documents as well as analyzing the studied theme, its way of presentation (dialogues) and the pre-textual elements (book cover, preface, dedication, summary and reading prologues) in different editions with the purpose to identify the formation of an infantile reader. For attaining our objectives, an approach of bibliographic and documental research was carried out. For the first one, the theoretical fundamentals were based on investigations about Reading History understood as social and cultural practice. Whereas, for the second one, the emphasis was on pieces of research accomplished in the Real Gabinete de Leitura Português (Royal Portuguese Office of Reading) and in the Biblioteca Nacional (National Library), in 2011 and 2012. Furthermore, the internet search for finding integral versions of the works was registered. The research revealed the following facts: the didactic compendia, in general, originated from France, had an essential role concerning the reader s formation, being indicated for teaching by the authorities, and also mentioned in other sources of research, such as bookstore catalogs, libraries and newspapers, presenting, therefore, other appropriation ways of these printings. With reference to content presentation, it was perceived the recurrence of the tradition of dialogs and themes focusing on moral, virtue and civility also usual in other books previous to the studied compendia. In this way, the guarantee that the reader s formation would be fulfilled from the conceptions that the society of that era anticipated, it occurred by means of the authorities´ discourses as well as by the directions presented by the authors of the compendia.